Penerapan Problem Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis Siswa IPS Kelas VII - Helni Laode; Radia Hafid; Ardiansyah; Meyko Panigoro; Rieriend Koniyo (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to improve students’ critical thinking skills through the implementation of the Problem-Based Learning (PBL) model in Social Studies for seventh-grade students at SMP Negeri 1 Suwawa. This research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 27 seventh-grade students, comprising 11 male and 16 female students. Data were collected through Higher-Order Thinking Skills (HOTS)-based essay tests designed according to critical thinking skill indicators aligned with the learning topics. The results of the study indicate that the implementation of the Problem-Based Learning (PBL) model effectively improves students’ critical thinking skills. This is evidenced by the increase in students’ average scores in each learning cycle. In the pre-cycle stage, the average score of students’ critical thinking skills was 64, categorized as low. After the implementation of PBL in Cycle I, the average score increased to 73, categorized as moderate. Furthermore, in Cycle II, the average score improved to 82, categorized as high. These findings demonstrate that the Problem-Based Learning model is effective in enhancing students’ critical thinking skills and encouraging more active participation in the learning process.